2014
DOI: 10.1002/adma.201305981
|View full text |Cite
|
Sign up to set email alerts
|

Record High Electron Mobility of 6.3 cm2V−1s−1 Achieved for Polymer Semiconductors Using a New Building Block

Abstract: A new electron acceptor building block, 3,6-di(pyridin-2-yl)pyrrolo[3,4-c ]pyrrole-1,4(2H ,5H)-dione (DBPy), is used to construct a donor-acceptor polymer, PDBPyBT. This polymer exhibits a strong self-assembly capability, to form highly crystalline and oriented thin films with a short π-π stacking distance of 0.36 nm. PDBPyBT shows ambipolar charge-transport performance in organic thin-film transistors, reaching a record high electron-mobility value of 6.30 cm(2) V(-1) s(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
387
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(400 citation statements)
references
References 60 publications
11
387
1
1
Order By: Relevance
“…[30] Similar efforts have been devoted to improving n-channel polymer semiconductors, with the performances of n-type devices still lagging behind their p-channel counterparts. [31][32][33][34][35][36] The main obstacle that has traditionally prevented the improvement of electron transporting polymers is the presence of trap sites forming at around −3.8 to −4.0 eV, mainly associated with hydrogenated oxygen, which complicates the design of conjugated polymers because of the requirement for a lowest unoccupied molecular orbital (LUMO) energy level that lays below this range. [37] In the recent past, different solutions have been proposed, among which a remarkably well performing solution-processable n-type polymer reported by Yan et al, based on a naphthalene diimide (NDI) acceptor moiety (referred to as PNDI2OD-T2) and easily achieving fieldeffect mobilities in the 0.1 to 1 cm 2 V −1 s −1 range, represented a breakthrough in the development of n-channel organic polymeric semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Similar efforts have been devoted to improving n-channel polymer semiconductors, with the performances of n-type devices still lagging behind their p-channel counterparts. [31][32][33][34][35][36] The main obstacle that has traditionally prevented the improvement of electron transporting polymers is the presence of trap sites forming at around −3.8 to −4.0 eV, mainly associated with hydrogenated oxygen, which complicates the design of conjugated polymers because of the requirement for a lowest unoccupied molecular orbital (LUMO) energy level that lays below this range. [37] In the recent past, different solutions have been proposed, among which a remarkably well performing solution-processable n-type polymer reported by Yan et al, based on a naphthalene diimide (NDI) acceptor moiety (referred to as PNDI2OD-T2) and easily achieving fieldeffect mobilities in the 0.1 to 1 cm 2 V −1 s −1 range, represented a breakthrough in the development of n-channel organic polymeric semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…With impedance spectroscopy on the finger-gate system, the mobility measurement is decoupled from charge injection and the true mobility in the transistor channel could be extracted. In some devices where record mobilities are measured, also a contact resistance is present [4]. Likely these mobilities are therefore underestimated and higher values may be obtained with the method presented in this paper.…”
Section: Contactless Mobility Measurementmentioning
confidence: 84%
“…Especially n-type and ambipolar polymers recently made strong progression [3][4][5][6][7][8]. However, as the channel resistance decreases due to the increase of organic semiconductor mobilities, contact resistances often become the bottleneck for the total device performance [1,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Sun et al reported the highest electron mobility of 6.3 cm 2 V -1 s -1 by combining pyridine with DPP which leads to highly crystalline polymers and oriented thin films. 24 Coupling DPP to selenophene has resulted in higher hole and electron mobilities (1.62 and 0.14 cm 2 V -1 s -1 ) compared to their thiophene counterparts. 25,26,27 DPP-vinylene and selenophene-vinyleneselenophene based copolymers have shown electron mobilities of ~0.05 cm 2 V -1 s -1 23 and hole mobilities as high as 4.97 cm 2 V -1 s -1 .…”
Section: Introductionmentioning
confidence: 99%